Onosma juliae (Boraginaceae), a new species from southern Turkey, with remarks on the systematics of Onosma in the Irano-Turanian region - Cecchi, Lorenzo; Coppi, Andrea; Selvi, Federico (Phytotaxa, 2016)
The new species Onosma juliae is described and illustrated based on specimens collected in the westernmost part of the Taurus range in southern Anatolia (Turkey, Karaman province). Differences with the putatively more closely related species are briefly discussed, and a synthetic but comprehensive key to the Irano-Turanian members of the genus known to date is provided to allow the identification of the major species group.